Spatial-temporal dynamics and evolution of ecological security in a rapid urbanization city, Southwest China - Dai, Yunchuan; Diao, Yuying; Dai, Chongyang; Li, Yi; Sun, Guiyan; Zahoor, Babar; Li, Dayong (Frontiers in Ecology and Evolution, 2022)
The main goal of constructing ecological security patterns (ESPs) is to identify ecological sources, corridors and nodes that play significant roles in sustainable development on a regional scale. Although there are many studies on the construction of ESPs, there is no consensus in terms of research methodology and systematic frameworks for integrated landscape management. Based on land use data from 2000, 2010, and 2020 of Chongqing Municipality in southwest China, we evaluated the spatial-temporal variation of ESPs by integrating InVEST and Circuit Theory. Results showed that: (a) Habitat quality varied through space, with habitat quality being lower in the western and central regions and higher in the southeastern and northeastern regions. (b) The area of lower quality habitat across different time periods was more than 46%, and habitat quality over the last two decades has generally been low with no significant improvement. (c) From 2000 to 2020, ecological sources were primarily distributed in the mountainous areas with high habitat quality and fractional vegetation coverage in the northeast and southeast. The regions identified ecological sources in 2000, 2010 and 2020 accounted for 31.37%, 33.53% and 32.7% of Chongqing Municipality, respectively. (d) The ESPs were composed of ecological sources dominated by forests, connected by continuous ecological corridors. The current ESPs of Chongqing Municipality included 20 ecological nodes, 17 continuous ecological corridors and 23 ecological sources. We strongly suggest the local governments strengthen the protection of the identified ecological nodes, ecological corridors, ecological sources, and protection gaps, and focus on strengthening the construction and management of the ecological corridor network system to promote species diffusion and gene exchange. Our findings are helpful for policy makers to introduce appropriate measures to objectively guide urban expansion via rational and sustainable development of land resources and improve the level of ecological security for Chongqing Municipality.